Legal Protection for Citizens Affected by Waste Disposal of PT. Rayon Utama Makmur - Alya Citra Cahya Pratiwi; Hartiwiningsih (MultiTech Publisher, 2023)
It started with residents' concerns who felt that the smell was not fresh, which tended to be rotten every day, which came from the waste produced by PT. Rayon Utama Makmur (PT. RUM). This unrest then gave rise to a movement from local residents to demand the dismissal of PT. Rayon Utama Makmur (PT. RUM). These demands led to quite a long road until the residents were furious and put up a blockade to close the entrance to PT. Rayon Utama Makmur (PT. RUM). Then the next action was that the residents also met with the local Regional People's Representative Council (DPRD) in the hope of resolving the problem. Not only that, residents have also met the Regent of Sukoharjo to demand the dismissal of PT. Rayon Utama Makmur (PT. RUM). This research was conducted by examining Law no. 32 of 2009 concerning Environmental Protection and Management as partially amended by Law Number 6 of 2023 concerning Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation (UU No. 32/2009 in conjunction with Law No. 6/ 2023) as the legal basis for this policy. While the regulations clearly regulate them, in reality they cannot provide justice to the victims of criminalization of environmental activists. The author hopes to be able to provide an in-depth understanding regarding the policies that have been regulated in this Law and to be able to provide input regarding law enforcement in handling environmental cases in Indonesia.